PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR MURID SMP - Eka Fara Fadiyah; Elok Sudibyo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to describe the improvement of students' cognitive learning outcomes, learning implementation, and student responses after the implementation of the Group Investigation (GI) cooperative learning model. The research method in this study is a quantitative method using a pre-experimental design with a one-group pretest-posttest design. The subjects in this study were 30 students of class VII-A of SMPN 1 Paciran. The instruments used in this study were pretest and posttest assessment sheets, learning implementation observation sheets, and student response questionnaire sheets. The results of this study indicate that the implementation of the Group Investigation (GI) learning model can improve student learning outcomes with an N-Gain value of 0.47 which is included in the moderate category. The results of the paired t-test show a significance value <0.001, which means there is a significant difference between the pretest and posttest scores. The magnitude of the influence is indicated by the effect size value of 4.72 which is in the very large category. The implementation of learning is classified as very good, with 23 of 25 aspects obtaining a mode of 4 (very good) and 2 aspects obtaining a mode of 3 (good). Furthermore, student responses to the learning process were in the very good category, with an average percentage of 84.13%. Thus, the Group Investigation (GI) cooperative learning model has a very strong impact on improving junior high school students' learning outcomes on the topic of matter and its changes.